Molecular Characterization of Thyroid Follicular Lesions in the Era of “Next-Generation” Techniques - Rossi, Esther Diana; Locantore, Pietro; Bruno, Carmine; Dell’Aquila, Marco; Tralongo, Pietro; Curatolo, Mariangela; Revelli, Luca; Raffaelli, Marco; Larocca, Luigi Maria; Pantanowitz, Liron; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2022)
It is unequivocally recognized that thyroid nodules are frequently detected in the adult population and mostly characterized by benign lesions (up to 70% of them), with only 5%–15% malignant lesions. The evaluation of thyroid lesions with fine-needle aspiration cytology (FNAC) represents one of the first and most useful diagnostic tools in the definition of their nature. Despite the fact that the majority of thyroid lesions are correctly diagnosed as either benign (70%–75%) or malignant (5%–10%) entities, the remaining nodules (20%–25%) represent the “gray zone” of follicular lesions, which belong to indeterminate categories, according to the different classification systems. This indeterminate group of lesions includes both benign and malignant entities, which cannot be easily discriminate with morphology alone. In these last decades, the increasing role of molecular testings, feasibly performed on cytological material combined with the discoveries of specific genetic alterations in the field of thyroid pathology, has opened the pace to their more accurate and specific contribution on cytology. In fact, in 2015, in the revised management guidelines for patients with thyroid nodules and well-differentiated thyroid cancers (WDTCs), the American Thyroid Association (ATA) confirmed the performance of molecular testing in thyroid indeterminate cytology, and the same performance was addressed in recent update of the management of thyroid nodules in the second edition of the Bethesda system for reporting thyroid cytopathology (TBSRTC). In the current review, we discuss the role of molecular tests for the different thyroid diagnostic categories of the Bethesda system for reporting thyroid cytopathology, mostly focusing our attention on the follicular and indeterminate lesions.